A week-long instructional design approach to teach postoperative pain management knowledge among Afghan anesthesiology faculty: a potential global health teaching blueprint - Alberto E Ardon; Julia L Weinkauf; Solen Feyissa; Carolyn M Porta (Inishmore Laser Scientific Publishing Ltd, 2020)
# Background Anesthesia-focused short courses might be an effective and sustainable way to further the ongoing training and evidence-based practice skills of anesthesia professionals in low- and middle-income countries (LMICs). Instructional design, the process by which formalized learning theory is incorporated into education planning and delivery, is a tool that can strengthen learning in these short courses. As part of an ongoing multilateral project between the University of Minnesota (UMN) and Kabul University of Medical Sciences (KUMS), this project sought to identify the feasibility and potential educational impact of a newly designed postoperative analgesia short-course employing instructional design principles. The Afghan faculty learners' subjective viewpoint of the short course experience was also investigated and is described in this article. # Methods Afghan learners and United States based faculty met in Bangalore, India in August 2018 for this short course. During the 6-day course, learners participated in didactics and workshops discussing regional anesthesia techniques, multimodal analgesia, safety, pain assessment and management, and the influence of ethno-cultural context on pain control. Interactive games, model-based nerve block simulations, and flipped classroom approaches were educational strategies used in the course. The Afghan faculty also participated in instructional design workshops designed to strengthen their teaching skills for use with both students and faculty colleagues. Pretests, posttests, and opinion surveys were completed by the Afghan faculty learners. # Results All learners completed the course with full participation. A median of 5 out of 10 technical questions were answered correctly by the learners on the pretest; this score improved to a median of 6.5 on the posttest. The number of learners who ranked their understanding of the role of regional anesthesia in their perioperative care practice as "very well" increased from 2 to 5 faculty. Likewise, the number of learners who described their understanding of postoperative pain and their ability to perform regional anesthesia as "not well at all" decreased from 2 to 0 in both categories. Further, the majority of the participants agreed that at the end of the course their ability to understand and apply instructional design concepts had improved. # Conclusions The short course in postoperative pain management appeared to improve short-term knowledge among Afghan faculty participants. Afghan faculty had a favorable opinion of the course and increased confidence in their ability to use instructional design best practices. The results of this project suggest that short courses based in instructional design can be useful and effective for short-term knowledge gain in an LMIC setting such as Afghanistan.